Effects of head-up vs. supine CPR on cerebral oxygenation and cerebral metabolism – a prospective, randomized porcine study. (July 2018) - Putzer, Gabriel; Braun, Patrick; Martini, Judith; Niederstätter, Ines; Abram, Julia; Lindner, Andrea Katharina; Neururer, Sabrina; Mulino, Miriam; Glodny, Bernhard; Helbok, Raimund; Mair, Peter
Abstract: Background: Recent studies have shown that during cardiopulmonary resuscitation (CPR) head-up position (HUP) as compared to standard supine position (SUP) decreases intracranial pressure (ICP) and increases cerebral perfusion pressure (CPP). The impact of this manoeuvre on brain oxygenation and metabolism is not clear. We therefore investigated HUP as compared to SUP during basic life support (BLS) CPR for their effect on brain oxygenation and metabolism. Methods: Twenty pigs were anaesthetized and instrumented. After 8 min of cardiac arrest (CA) pigs were randomized to either HUP or SUP and resuscitated mechanically for 20 min. Mean arterial pressure (MAP), ICP, CPP, cerebral regional oxygen saturation (rSO2 ) and brain tissue oxygen tension (Pbt O2 ) were measured at baseline, after CA and every 5 min during CPR. Cerebral venous oxygen saturation (Scv O2 ) was measured at baseline, after CA and after 20 min of CPR. Cerebral microdialysis parameters, e.g. lactate/pyruvate ratio (L/P ratio) were taken at baseline and the end of the experiment. Results: ICP was significantly lower in HUP compared to SUP animals after 5 min (18.0 ± 4.5 vs. 24.1 ± 5.2 mmHg; p = 0.033) and 20 min (12.0 ± 3.4 vs. 17.8 ± 4.3 mmHg; p = 0.023) of CPR. Accordingly, CPP was significantly higher in the HUP group after 5 min (11.2 ± 9.5 vs. 1.0 ± 9.2 mmHg; p = 0.045) and 20 min (3.4 ± 6.4 vs. −3.8 ± 2.8 mmHg; p = 0.023) of CPR. However, no difference was found in rSO2, Pbt O2, Scv O2 and L/P ratio between groups after 20 min of CPR. Conclusion: In this animal model of BLS CPR, HUP as compared to SUP did not improve cerebral oxygenation or metabolism.